Data analysis for psychology - Dunbar, George (George L.) (London : Arnold ; New York : Distributed by St. Martin's Press, 1998)
1. Psychology--data analysis
Includes index.
Faculty
Keywords: Psychometrics; Psychology -- Research -- Methodology